China as a target for direct foreign investments - Zabiełło Katarzyna (My University, 2006)
The aim of the project is to analyze why enterprises invest in foreign countries and to examine why China has recently become the target of massive Foreign Direct Investments. The project is divided into two parts. The first part gives full description of the framework of OLI, its origins and why it is the most adequate for the purpose of the project. Further it deals with the theory of foreign direct investments, explains the motives behind FDI activities and the benefits for both – the host and the investor. Second part provides the characteristic of FDI in China. Further it gives a detailed analysis of China as a recipient of FDI in attempt to answer the question why has China been so successful in attracting FDI. In the end the positive and negative results of the impact of massive direct investment in China are briefly summarized.
Chiny jako cel bezpośrednich inwestycji zagranicznych
Keywords: foreign direct investments; China; globalisation; OLI; WTO